Desenvolvimento de livro paradidático para a divulgação científica sobre a biodiversidade de abelhas brasileiras - Boeing, Guilherme Andrade Neto Schmitz (Universidade Federal de São Carlos, 2021)
The use of paradidatic books in science teaching has been shown to be effective in helping students understand and visualize social problems. Currently, Brazil and the world are facing the biggest population decline of angiosperm pollinators thanks to anthropic actions such as deforestation, fires, urbanization, monocultures and pesticides. Thus, the proposal of this studt was to elaborate a paradidatic book on the biodiversity of native bees, in order to use it as material for scientific dissemination. The survey of information and the selection of species for the composition of the book's plot were carried out using the Moure Bee Catalog (http://moure.cria.org.br/index) in conjunction with the Global Biodiversity Information platform Facility (GBIF - https://www.gbif.org/pt/). With the species defined, realistic morphological images were produced using the Adobe Illustrator software, made available by Adobe Systems, and the production of scenarios using the CorelDRAW® Graphics Suite 2020 software. Finally, the Microsoft PowerPoint software was used for the end production of the paradidatic book. After conducting a bibliographic survey of information about native bee species, it was possible to select those that would compose the book based on their biodiversity characteristics. With that, a script was elaborated and, consequently, the scenarios and morphological drawings were produced and finalized. The final layout of the book was carried out and the title “Beeodiversidade” was chosen. With all these processes, it can be concluded that there was a successful development of a paradidatic book for teaching about the biodiversity of Brazilian bees which could expand the reader's knowledge on the subject.
Development of a paradidatic book for scientific dissemination on the biodiversity of brazilian bees
Keywords: Paradidático; Abelhas-nativas; Diversidade; Ensino; Educational; Native Bees; Diversity; Teaching; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO